2022
DOI: 10.3390/nano12030395
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical and Tribological Properties of Advanced Layered WN/MeN (Me = Zr, Cr, Mo, Nb) Nanocomposite Coatings

Abstract: Due to the increased demands for drilling and cutting tools working at extreme machining conditions, protective coatings are extensively utilized to prolong the tool life and eliminate the need for lubricants. The present work reports on the effect of a second MeN (Me = Zr, Cr, Mo, Nb) layer in WN-based nanocomposite multilayers on microstructure, phase composition, and mechanical and tribological properties. The WN/MoN multilayers have not been studied yet, and cathodic-arc physical vapor deposition (CA-PVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…It is demonstrated that the as-deposited films have many surface defects, namely droplets, particles and craters, which are mainly caused by liquid droplets emitted from the surface of the Nb and Ag targets during film deposition process. The defect density on the surface of NbN-Ag and NbN/NbN-Ag films is higher than that of NbN film, which is due to the lower melting point of Ag (962 °C) than Nb (2468 °C), and hence the Ag droplets are formed more easily [ 27 ]. As can be seen from the insets of Figure 1 b, the large Ag droplets and a relatively small Nb droplet are distributed on the Ag-doped film surface.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that the as-deposited films have many surface defects, namely droplets, particles and craters, which are mainly caused by liquid droplets emitted from the surface of the Nb and Ag targets during film deposition process. The defect density on the surface of NbN-Ag and NbN/NbN-Ag films is higher than that of NbN film, which is due to the lower melting point of Ag (962 °C) than Nb (2468 °C), and hence the Ag droplets are formed more easily [ 27 ]. As can be seen from the insets of Figure 1 b, the large Ag droplets and a relatively small Nb droplet are distributed on the Ag-doped film surface.…”
Section: Resultsmentioning
confidence: 99%
“…The multilayer is composed of the alternating layers of darker TiSiN and brighter WN x . In backscatter electron imaging, heavier elements can backscatter primary electrons stronger than light elements [25,26]. Hence, heavier elements appear brighter.…”
Section: Cross-sectionsmentioning
confidence: 99%
“…Furthermore, as can be seen, magnetron sputtering is the predominant deposition technique. In our previous study, we successfully synthesized WN/ZrN, WN/CrN, WN/MoN, and WN/NbN coatings under the same deposition conditions using the CA-PVD method and comprehensively characterized them . This approach aimed to elucidate the system that exhibited the best tribomechanical properties.…”
Section: Introductionmentioning
confidence: 99%